Revisit of fluoroquinolone and azithromycin susceptibility breakpoints forSalmonella entericaserovar Typhi. Issue 7 (July 2016) - Das, Surojit; Ray, Ujjwayini; Dutta, Shanta
Abstract : N/A: In recent years, increase in occurrence of fluoroquinolone (FQ)‐resistant S almonella Typhi isolates has caused considerable inconvenience in selecting appropriate antimicrobials for treatment of typhoid. The World Health Organization (WHO) recommends azithromycin for the empirical treatment option of uncomplicated typhoid. The CLSI updated the breakpoints of disc diffusion (DD) and MIC results of FQs and azithromycin for Salmonella Typhi in 2015, but DD breakpoints of ofloxacin and levofloxacin were not included. In this study, the inhibition zone diameters and MICs of nalidixic acid, ciprofloxacin, ofloxacin, levofloxacin and azithromycin were determined in Salmonella Typhi Kolkata isolates ( n =146) over a 16‐year period (1998 to 2013) and the data were compared with the available CLSI breakpoints. Very major error and major error (ME) of FQs were not observed in the study isolates, but the minor error of ciprofloxacin (15.8 %) and ME of azithromycin (3.5 %) exceeded the acceptable limit. A positive correlation between MICs of FQ and mutations in the quinolone‐resistance‐determining region (QRDR) showed the reliability of MIC results to determine FQ susceptibility of Salmonella Typhi ( n =74). Isolates showing decreased ciprofloxacin susceptibility (MIC 0.125‐0.5 μg ml −1 ) were likely to have at least one mutation in the QRDR region. The results on DD breakpoints of ofloxacin (resistant, ≤15 mm; intermediate, 16‐24 mm, and susceptible, ≥25 mm) and levofloxacin (resistant, ≤18 mm; intermediate, 19‐27 mm, and susceptible, ≥28 mm) corroborated those of earlier studies. In view of the emerging FQ‐ and azithromycin‐resistant Salmonella Typhi isolates, DD and MIC breakpoints of those antimicrobials should be revisited routinely.